English: english - Yayu Nidaul Fithriyyah; Suis Galischa Wati; Haryani; Atikah Kurnia Alda (Poltekkes Kemenkes Semarang, 2026)
Background: Ethical competence is crucial for nurses, particularly in disaster situations, where they face numerous challenges such as limited resources, triage decisions, and patient confidentiality. While various instruments have been developed to assess nurse competencies in disaster contexts, none specifically address ethical competence. Purpose: This study aims to develop and determine the psychometric properties of the Ethical Competence Questionnaire in Disasters for Nurses (ECQD-N). Methods: A mixed-method sequential exploratory design, consisting of two phases, was used. In Phase I, the ECQD-N was developed through in-depth interviews and focus group discussions with disaster-experienced nurses, based on the ethical competence literature. Phase II involved testing the psychometric properties of the instrument through a content validity test, a pilot study, and exploratory factor analysis (EFA). The reliability of the instrument was assessed using Cronbach’s alpha. Results: The final sample for the psychometric testing phase consisted of 250 nurses. The Cronbach’s alpha value ranges from 0.774 to 0.902, indicating good reliability. Factor analysis identified four factors: ethical knowledge, ethical skills, ethical attitudes, and ethical issues, collectively explaining 61.655% of the total variance. The final scale with 22 items and four subscales, namely, ethical attitudes (9 items), ethical knowledge (5 items), ethical skills (4 items), and ethical issues (4 items). Conclusion: The ECQD-N is an acceptable tool to measure nurses' ethical competence in disasters reliably. Further research is needed to examine the underlying constructs and their latent variables by conducting a Confirmatory Factor Analysis (CFA). Keywords: Ethics; disaster; nurses; psychometrics testing